Model Prediksi Kepailitan Bank Umum di Indonesia - Prajitno, Teguh (Jurnal Trikonomika, 2009)
The objective of this study is to obtain an empirical evidence of bank financial ratio that can be used to identify the bankâs behavior where it is categorized in to bankrupt or successful one. There are two methods used in predicting bankruptcy namely Linier Discriminatory Method (LDM) and Logistic Regression Method (LRM). The independent coefficient variable of this study is dummy variable that is estimated through simultaneous approach for Linier Discriminatory and Maximum Likelihood for Logistic Regression.The research findings indicate that liquidity ratio is the best discriminator to distinguish whether a bank is successful or bankrupt. Moreover, the present study indicate that Linier Discriminatory Method is relatively better than Logistic Regression Method. It can be seen from variable value of the three ratios that enable to distinguish successful bank or bankrupt bank. Nevertheless, mean score of correct estimate of Logistic Regression Method is higher than correct estimate of Linier Discrimatory Method. Whereas, the present study also indicate that Logistic Regression Method has no significant financial ratio to identify the distinction of successful or bankrupt bank.